Sign language use in healthcare: professionals’ insight - Qadhi,Omaimah (PeerJ, 2025)
Background and Aim Communication using sign language (SL) between health care providers (HCPs) and deaf and/or hearing-impaired (DHI) patients was reported to be difficult and oftentimes results in a compromised delivery of quality health care to patients. This study surveyed Saudi health care providers on their perception of SL knowledge on the provision of high-quality care to DHI patients. Methods This was a cross-sectional descriptive study among HCPs in different health and primary care centers in Riyadh, Saudi Arabia. The questionnaire was distributed officially by the Department of Surveys of King Saud University to target HCPs via email and through WhatsApp. Results A total of 238 HCPs were included in the study, of whom 180 (75.6%) were nursing professionals and 58 were from other health specialties. Only 15 (6.3%) of HCPs claimed to have received formal training in SL. Majority of the HCPs (n = 165, 69.3%) perceived that knowledge in SL is very important for communication with DHI patients and their families, whereas 65 (27.3%) perceived SL as somewhat important. Nurses believed that the quality of health service and care to deaf and/or hearing-impaired (DHI) patients is impacted by the inability of HCPs to communicate effectively and deliver high-quality care without the knowledge. Nursing professionals believed that knowledge of SL will improve the quality of care provided to DHI patients compared to other HCPs (97.2% vs. 87.9%, p = 0.005). Conclusion In order to provide DHI patients with high-quality healthcare, nurses believe that understanding SL is essential. Few nurses received formal training and few have adequate knowledge in SL. There is a need to provide nurses and HCPs adequate training in SL to improve communication with DHI patients and enhance DHI inclusivity in their management in line with the World Health Organization’s Universal Health Coverage and “health care for all”.
Keywords: Sign language; Nursing; Quality of care delivery; Communication; Workplace; Deaf; Hearing-impaired; Healthcare providers; Special needs